Ultrasound-activated nanomaterials for sonodynamic cancer theranostics. Issue 6 (June 2022) - Wu, Nan; Fan, Ching-Hsiang; Yeh, Chih-Kuang
Graphical abstract: This review discusses the applications of SDT in cancer, summarized and classified by their anti-tumor mechanism. Highlights: Sonodynamic therapy is a promising anti-tumor modality that noninvasively yields reactive oxygen species near tumor cells. The development of sonosensitizers that are not photosensitive is critical. Sonodynamic therapy can play a multifaceted role in improving the outcome of tumor treatment. Several clinical studies have demonstrated that sonodynamic therapy could be a good adjunct to other therapies. Abstract: Despite intensive efforts to develop diagnostic and therapeutic tools, the successful treatment of cancer is still hampered by the obscure boundary between cancerous cells and normal cells, recurrence of the cancer, and the development of drug resistance during chemotherapy. In recent years, sonodynamic therapy (SDT), employing therapeutic ultrasound with sonosensitizers, has attracted attention as a potentially promising approach for cancer therapy. This review describes the current understanding of the mechanisms and the preclinical and clinical efficacy of SDT-based applications in tumors, providing an insight into the therapeutic potential offered by SDT. The limitations and future directions of this emerging treatment are also discussed.